A classification of indecomposable Quasi-Frobenius rings I. Issue 12 (2nd December 2019) - Birkenmeier, Gary F.; Almallah, Omar
Abstract: This is the first in a series of papers on the classification of indecomposable QF-rings. Our classification is based on the concepts of a nilary ring and the essentiality of the traces of idempotent generated right ideals. Recall that a ring R is called nilary if AB = 0 then A is nilpotent or B is nilpotent for all ideals A and B of R . In this paper, we classify the nilary QF-rings.